ANALISIS PENGARUH SUDUT PUNCH TERHADAP PROSES V BENDING 90 DERAJAT - Shangra, Kevin Dwiva; Arifin, Fatahul; Arnoldi, Dwi (Politeknik Negeri Sriwijaya, Indonesia, 2025)
Springback in plate bending makes the bending angle results incompatible with the punch used due to the nature of steel material elasticity. This research aims to find an angle that is close to a 90-degree angle on ST 37 low carbon steel material using 6 punch pieces that vary with 3 different angles and 2 radii and 1 die. This bending test is carried out with the V bending process and uses a manual hydraulic press with a capacity of 2 tons as a press to perform the bending process. The test results on the material will be seen from the springback results and also the punch with what angle can produce an angle close to 90 degrees. The results of the punch angle of 90 radius 1 of 5 times testing the average value is 92.93 with a springback of 2.93 and the value that is very close to 90 degrees is at an angle of 87.80 radius 1 with a result of 89.95 degrees and to get the maximum angle results can use the springback formula after testing and from the springback results of the 92.93 angle results, it can be calculated and the result of the punch angle that must be used is 87.6 degrees. The result of v bending is quite close to the 90 degree angle of 89.80 degrees